GAMBARAN RASIONALITAS PENGGUNAAN OBAT DIARE PADA BALITA PENDERITA DIARE AKUT - Muhammad Akib Yuswar; Sofia Futria Wulandari; Nera Umilia Purwanti (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Diarrhea is the highest causes of death for children under five years of age in Indonesia 2019. Dehydration is one of the main causes of death in diarrhea. This study aims to find out the rationality for the use of diarrhea drugs in toddlers with acute diarrhea based on the degree of dehydration at the Sultan Syarif Mohamad Alkadrie Hospital Pontianak in 2020. The method used in this study is descriptive observational with a cross-sectional design. Data collection was carried out retrospectively, the sample was determined by purposive sampling method through searching medical record data. The results showed that the percentage rationality of using diarrhea drugs for acute watery diarrhea without dehydration based on the criteria for the right indication of (100%), the right patient of (100%), the right drug selection of (100%), the right dose of (78.57%), and the right duration of treatment of (100%); the percentage rationality of using diarrhea drugs for acute watery diarrhea with mild/moderate dehydration based on the criteria for the right indication of (100%), the right patient of (100%), the right drug selection of (62,40%), the right dose of (47.93%) and the right duration of treatment of (76.86 %) and the percentage rationality of using diarrhea drugs for acute watery diarrhea with severe dehydration based on the criteria for the right indication of (100%), right patient of (100%), the right drug selection of (90%), the right dose of (65%) and the right duration of treatment of (90%). The overall conclusion of this study is that the use of diarrhea drugs in toddlers is rational, but it needs to be considered again for drug dosing, especially in acute liquid diarrhea with mild/moderate dehydration because it has the smallest percentage of 47.93%.